Method for preventing aluminum nitride ceramic substrate from moisture absorption and hydrolysis in DCB and AMB

Nitrogen was solved by immersing the etched copper-clad ceramic substrate in an immersion solution mixed with n-dodecyl trimethoxysilane solution and pure water to form a covalent bonded n-dodecyl siloxane coating layer The problem of moisture absorption and hydrolysis of aluminum-chemical ceramic substrates in humid environments has achieved effective moisture-proofing of copper-clad ceramic substrates and improved product performance and reliability.

CN119485952APending Publication Date: 2025-02-18四川富乐华半导体科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411157747.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, aluminum nitride ceramic substrates are prone to moisture absorption and hydrolysis in humid environments, resulting in damage to the structure of copper clad ceramic substrates, degradation of mechanical properties, and affecting reliability.

Method used

By immersing the etched copper-clad ceramic substrate in an immersion solution mixed with n-dodecyl trimethoxysilane solution and pure water, the surface of the exposed aluminum nitride ceramic substrate is formed with covalent bonded n-dodecyl silicon on the surface of the exposed aluminum nitride ceramic substrate. Oxane cladding.

Benefits of technology

Effectively prevent moisture absorption and hydrolysis of aluminum nitride ceramic substrates, improve moisture resistance of copper clad ceramic substrates, and improve product performance and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119485952A_ABST
    Figure CN119485952A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of copper-clad ceramic substrate preparation, in particular to a method for preventing an aluminum nitride ceramic substrate from moisture absorption and hydrolysis in DCB and AMB, and the copper-clad ceramic substrate is subjected to sintering, pretreatment cleaning, pattern transfer, etching and hydrolysis treatment after etching. According to the invention, through hydrolysis and dehydration reactions of n-dodecyltrimethoxysilane, covalent bonds of hydroxyl groups and hydroxyl groups on the surface of the aluminum nitride ceramic substrate exposed after etching of the copper-clad ceramic substrate are combined to form a compact n-dodecylsiloxane coating layer, so that moisture absorption and hydrolysis prevention effects are achieved, and the moisture-proof effect is good; and the product performance and reliability are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of copper-clad ceramic substrate preparation, and in particular to a method for preventing aluminum nitride ceramic substrates from absorbing moisture and hydrolyzing in DCB and AMB. Background Art

[0002] At present, the copper-clad ceramic substrates (DCB and AMB) in the industry all use aluminum nitride ceramic substrates as the substrate. However, due to the unique chemical properties of aluminum nitride, it will absorb moisture and hydrolyze in a humid environment, AlN+H2O→Al(OH)3+NH3, so that the aluminum nitride ceramic substrate exposed after etching in the copper-clad ceramic substrate will undergo a hydrolysis reaction, which will destroy the structure of the entire copper-clad ceramic substrate, reduce its mechanical properties, and ultimately affect the reliability of the copper-clad ceramic substrate.

[0003] At the same time, copper-clad ceramic substrates are inevitably humid during transportation, storage and use. If the exposed aluminum nitride ceramic substrate is in a humid environment for a long time, it will inevitably absorb moisture and hydrolyze, causing the product performance and reliability to decline.

[0004] In the prior art, aluminum nitride powder is often treated for hydrolysis resistance. When an aluminum nitride ceramic substrate made of aluminum nitride powder is used as a substrate for a copper-clad ceramic substrate, the aluminum nitride ceramic substrate made of aluminum nitride powder has a reduced moisture absorption and hydrolysis resistance after sintering, pre-treatment cleaning, pattern transfer, etching, etc. The copper-clad ceramic substrate is not treated for moisture absorption and hydrolysis resistance as a whole, and only the copper surface is protected against oxidation. After etching the copper-clad ceramic substrate, the aluminum nitride ceramic substrate inside is exposed, thereby causing moisture absorption and hydrolysis. Currently, moisture-proof protection is only provided by basic means such as sealing in packaging, but the moisture-proof effect is poor, and it is impossible to perform a hydrolysis resistance treatment on the surface of the aluminum nitride ceramic substrate.

[0005] In view of this, this application is filed. Summary of the invention

[0006] The object of the present invention is to provide a method for preventing the aluminum nitride ceramic substrate from absorbing moisture and hydrolyzing in DCB and AMB, wherein the etched copper-clad ceramic substrate is immersed in an immersion solution mixed with a n-dodecyltrimethoxysilane solution of a specific formulation system and pure water, so that a covalently bonded n-dodecylsiloxane coating layer is formed on the exposed surface of the aluminum nitride ceramic substrate, thereby preventing the aluminum nitride ceramic substrate in the copper-clad ceramic substrate from absorbing moisture and hydrolyzing, and solving the above-mentioned problems existing in the prior art.

[0007] In order to solve the above technical problems, the present invention adopts the following solutions: A method for preventing aluminum nitride ceramic substrate from absorbing moisture and hydrolyzing in DCB and AMB, wherein the copper-clad ceramic substrate is sintered, pre-treated and cleaned, pattern transferred, and etched, and then subjected to anti-hydrolysis treatment after etching, wherein the anti-hydrolysis treatment comprises the following steps: Step 1: prepare n-dodecyltrimethoxysilane solution and allow to stand for sufficient pre-hydrolysis; Step 2: adding the pre-hydrolyzed n-dodecyltrimethoxysilane solution into pure water to obtain a soaking solution; Step 3: soaking the etched copper-clad ceramic substrate in a soaking solution; Step 4: heating and drying the copper-clad ceramic substrate soaked in step 3, so that a covalently bonded n-dodecylsiloxane coating layer is formed on the surface of the aluminum nitride ceramic substrate exposed in the copper-clad ceramic substrate.

[0008] The technical concept of this application is: After etching, the aluminum nitride ceramic substrate on the inner layer of the copper-clad ceramic substrate will be exposed. At this time, the exposed aluminum nitride ceramic substrate is immersed in an immersion solution prepared by a n-dodecyltrimethoxysilane solution and pure water. After heating treatment, a covalently bonded n-dodecylsiloxane coating layer is formed, thereby preventing the aluminum nitride ceramic substrate exposed after etching in the copper-clad ceramic substrate from absorbing moisture and hydrolyzing.

[0009] First, n-dodecyltrimethoxysilane, pure water and methanol are mixed to obtain a n-dodecyltrimethoxysilane solution, and the SiX methoxy groups connected to the silicon atom of n-dodecyltrimethoxysilane are hydrolyzed to generate n-dodecylsilanol.

[0010] Secondly, Si-OH in siloxane forms hydrogen bonds with -OH on the surface of the aluminum nitride ceramic substrate exposed in the copper-clad ceramic substrate.

[0011] Finally, the immersed copper-clad ceramic substrate is heated and dried under nitrogen conditions. During the drying process, Si-OH of n-dodecylsilanol reacts with -OH on the surface of the exposed aluminum nitride ceramic substrate to form a covalent bond between the n-dodecylsilanol and the aluminum nitride ceramic substrate exposed in the copper-clad ceramic substrate. At the same time, Si-OH between the n-dodecylsilanols also undergoes dehydration condensation and cross-linking. The two reactions proceed simultaneously, and finally a dense n-dodecylsiloxane coating layer is formed on the surface of the substrate, thereby preventing the aluminum nitride ceramic substrate from moisture absorption and hydrolysis.

[0012] In the dehydration reaction, the silanol generated by the hydrolysis of n-dodecyltrimethoxysilane on the interface contains 3 silanol groups, and only one silanol group is covalently bonded to the -OH on the surface of the aluminum nitride ceramic substrate; the remaining 2 Si-OH groups condense with other Si-OH groups in the n-dodecylsilanol generated by other hydrolysis and cross-link with each other, and finally form a dense n-dodecylsiloxane coating layer on the surface of the aluminum nitride ceramic substrate, which serves the purpose of preventing water decomposition and moisture absorption.

[0013] Further preferably, in the step 1, the mass fraction of the n-dodecyltrimethoxysilane solution is 15% to 20%.

[0014] More preferably, 15% to 35% by mass of n-dodecyltrimethoxysilane, 5% to 8% of pure water, and the remainder of methanol are uniformly mixed to obtain an n-dodecyltrimethoxysilane solution.

[0015] Specifically, water and methanol are both silane hydrolyzing agents, and adjusting the ratio of the two can control the hydrolysis rate of n-dodecyltrimethoxysilane and make the hydrolysis more complete.

[0016] Further preferably, the pH of the n-dodecyltrimethoxysilane solution is adjusted to 3.5-5.5.

[0017] More preferably, the standing time in step 1 is 10 min to 20 min.

[0018] Further preferably, in the step 2, the ratio of the pre-hydrolyzed n-dodecyltrimethoxysilane solution to pure water is 1-2:18-19.

[0019] Further preferably, in step three, the soaking time is 15 min to 25 min.

[0020] Further preferably, in step 4, heating and drying are performed under nitrogen protection conditions. Nitrogen protection conditions prevent copper oxidation.

[0021] More preferably, the drying temperature is 90°C to 150°C.

[0022] More preferably, the drying time is 45 min to 60 min.

[0023] The beneficial effects of the present invention are as follows: the present invention provides a method for preventing an aluminum nitride ceramic substrate from absorbing moisture and hydrolyzing in a DCB and an AMB, wherein a configuration system based on a specific n-dodecyltrimethoxysilane solution is used, a certain proportion of the n-dodecyltrimethoxysilane solution is mixed with pure water to obtain an immersion solution, and an aluminum nitride ceramic substrate exposed in an etched copper-clad ceramic substrate is immersed in the solution to hydrolyze the n-dodecyltrimethoxysilane to generate n-dodecylsilanol, and the n-dodecylsilanol undergoes a dehydration reaction during heating and drying, and one of the generated silanols is covalently bonded to a hydroxyl group on the surface of the aluminum nitride ceramic substrate, thereby forming a dense n-dodecylsiloxane coating layer on the surface of the aluminum nitride ceramic substrate exposed after the copper-clad ceramic substrate is etched, which plays a role in preventing moisture absorption and hydrolysis, has a good moisture-proof effect, and improves the product performance and reliability of the copper-clad ceramic substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic structural diagram of a covalently bonded n-dodecylsiloxane coating layer formed on the surface of an aluminum nitride ceramic substrate after etching the copper-clad ceramic substrate of the present invention.

[0025] Figure numerals: 1-aluminum nitride ceramic substrate, 2-copper cladding, 3-n-dodecylsiloxane coating layer. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The present invention provides a method for preventing aluminum nitride ceramic substrate from absorbing moisture and hydrolyzing in DCB and AMB, wherein the copper-clad ceramic substrate is sintered, pre-treated and cleaned, pattern transferred, and etched, and then subjected to anti-hydrolysis treatment after etching, wherein the anti-hydrolysis treatment comprises the following steps: Step 1: Prepare a 15% to 20% mass fraction of n-dodecyltrimethoxysilane solution and allow it to stand for sufficient pre-hydrolysis.

[0028] 15% to 35% by mass of n-dodecyltrimethoxysilane, 5% to 8% pure water, and the rest methanol are mixed uniformly to obtain a 15% to 20% by mass n-dodecyltrimethoxysilane solution, and the pH is adjusted to 3.5 to 5.5, and the solution is allowed to stand for 10 min to 20 min.

[0029] In this step, the SiX methoxy group connected to the silicon atom in n-dodecyltrimethoxysilane is hydrolyzed to generate n-dodecylsilanol.

[0030] Step 2: Add the pre-hydrolyzed n-dodecyltrimethoxysilane solution into pure water to obtain a soaking solution.

[0031] The ratio of the pre-hydrolyzed n-dodecyltrimethoxysilane solution to pure water in the immersion solution is 1~2:18~19.

[0032] Step 3: Soak the etched copper-clad ceramic substrate in a soaking solution for 15 minutes to 25 minutes.

[0033] In this step, SiOH in the siloxane forms hydrogen bonds with -OH on the surface of the aluminum nitride ceramic substrate after etching the copper-clad ceramic substrate for charge coordination.

[0034] Step 4: heating and drying the aluminum nitride ceramic substrate soaked in step 3.

[0035] The heating and drying is mainly carried out under nitrogen protection conditions, the drying temperature is 90℃~150℃, and the drying time is 45min~60min.

[0036] In this step, the -OH of n-dodecylsilanol forms a covalent bond with the -OH on the surface of the aluminum nitride ceramic substrate due to the dehydration reaction. Only one of the three silanols generated by the hydrolysis of n-dodecyltrimethoxysilane on the interface is bonded to the hydroxyl group on the surface of the aluminum nitride ceramic substrate, and the remaining two Si-OH condense with the Si-OH of the other n-dodecylsilanols generated by the hydrolysis and crosslink each other, and finally form a dense n-dodecylsiloxane coating layer on the surface of the aluminum nitride ceramic substrate, which prevents the aluminum nitride ceramic substrate from moisture absorption and hydrolysis.

[0037] After drying, the copper-clad ceramic substrate is cleaned, anti-oxidized, inspected and packaged.

[0038] Example 1 This embodiment 1 is a method for preventing aluminum nitride ceramic substrate from absorbing moisture and hydrolyzing in DCB and AMB, comprising the following steps: 1) Weigh 20% n-dodecyltrimethoxysilane, 8% pure water and 72% methanol and mix them evenly to obtain a 20% n-dodecyltrimethoxysilane solution. Adjust the pH to 3.5-5.5 and let it stand for 10-20 minutes to allow the solution to be fully pre-hydrolyzed. 2) Mixing a fully pre-hydrolyzed n-dodecyltrimethoxysilane solution with pure water to obtain a soaking solution in a ratio of 1-2:18-19, and soaking the etched copper-clad ceramic substrate in the soaking solution for 15-25 minutes; 3) The immersed copper-clad ceramic substrate is placed in a nitrogen oven and heated and dried under nitrogen conditions. The drying temperature is 90°C to 150°C and the drying time is 45min to 60min. At this time, a n-dodecylsiloxane coating layer is formed on the surface of the aluminum nitride ceramic substrate exposed after etching the copper-clad ceramic substrate.

[0039] Example 2 This embodiment 2 is a method for preventing aluminum nitride ceramic substrate from absorbing moisture and hydrolyzing in DCB and AMB, comprising the following steps: 1) Weigh 15% n-dodecyltrimethoxysilane, 5% pure water and 80% methanol and mix them evenly to obtain a 15% n-dodecyltrimethoxysilane solution. Adjust the pH to 3.5-5.5 and let it stand for 10-20 minutes to allow the solution to be fully pre-hydrolyzed. 2) Mix the fully pre-hydrolyzed n-dodecyltrimethoxysilane solution with pure water to make the ratio of n-dodecyltrimethoxysilane solution to pure water be 1-2:18-19 to obtain an immersion solution, and immerse the etched aluminum nitride ceramic substrate in the immersion solution for 15-25 minutes; 3) The immersed copper-clad ceramic substrate is placed in a nitrogen oven and heated and dried under nitrogen conditions. The drying temperature is 90°C to 150°C and the drying time is 45min to 60min. At this time, a n-dodecylsiloxane coating layer is formed on the surface of the aluminum nitride ceramic substrate exposed after etching the copper-clad ceramic substrate.

[0040] Comparative Example The main process flow of the comparative example of the present invention is: sintering of the copper-clad ceramic substrate → cleaning → pattern transfer → etching → cleaning and anti-oxidation → inspection and packaging, and no moisture absorption and hydrolysis treatment is performed after etching.

[0041] Performance Testing The test adopts high temperature and high humidity test for comparison, that is, under the conditions of temperature 85°C and humidity 85%, the substrate samples treated with Example 1, Example 2 and the comparative example are placed in a high temperature and high humidity test box. After 500h and 1000h, the ceramic substrate samples are compared to see whether hydrolysis occurs and the degree of hydrolysis. At each stage, the aluminum nitride on the substrate is taken separately to test its oxygen content. If the oxygen content increases, hydrolysis occurs.

[0042] Table 1 Comparison of oxygen content test in aluminum nitride ceramic substrate After etching the copper-clad ceramic substrate, the aluminum nitride ceramic substrate is exposed. When the aluminum nitride ceramic substrate is hydrolyzed, an ammonia smell is generated. According to Table 1, after being treated at high temperature and high humidity for 500 hours and 1000 hours respectively, the ceramic substrate samples in the comparative example respectively have an ammonia smell and an increased oxygen content, while the initial conditions and high temperature and high humidity treatment conditions of Example 1 and Example 2 remain unchanged, which means that the aluminum nitride ceramic substrate in the copper-clad ceramic substrate treated by the present invention effectively prevents moisture absorption and hydrolysis. Figure 1 As shown, the generated n-dodecylsiloxane coating layer is not limited to the surface of the aluminum nitride ceramic substrate after etching, but also includes other exposed surfaces of the aluminum nitride ceramic substrate.

[0043] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A method for preventing aluminum nitride ceramic substrates from absorbing moisture and hydrolyzing in DCB and AMB, characterized in that: The copper-clad ceramic substrate is sintered, pre-treated and cleaned, patterned and etched, and then subjected to an anti-hydrolysis treatment, wherein the anti-hydrolysis treatment comprises the following steps: Step 1: prepare n-dodecyltrimethoxysilane solution and allow to stand for sufficient pre-hydrolysis; Step 2: adding the pre-hydrolyzed n-dodecyltrimethoxysilane solution into pure water to obtain a soaking solution; Step 3: soaking the etched copper-clad ceramic substrate in a soaking solution; Step 4: heating and drying the copper-clad ceramic substrate soaked in step 3, so that a covalently bonded n-dodecylsiloxane coating layer is formed on the surface of the aluminum nitride ceramic substrate exposed in the copper-clad ceramic substrate.

2. A method for preventing aluminum nitride ceramic substrate from absorbing moisture and hydrolyzing in DCB and AMB according to claim 1, characterized in that: In the step 1, the mass fraction of the n-dodecyltrimethoxysilane solution is 15% to 20%.

3. The method for preventing aluminum nitride ceramic substrate from absorbing moisture and hydrolyzing in DCB and AMB according to claim 1, characterized in that: 15% to 35% by mass of n-dodecyltrimethoxysilane, 5% to 8% of pure water, and the remainder of methanol are mixed uniformly to obtain an n-dodecyltrimethoxysilane solution.

4. The method for preventing aluminum nitride ceramic substrate from absorbing moisture and hydrolyzing in DCB and AMB according to claim 1, characterized in that: The pH of the n-dodecyltrimethoxysilane solution is adjusted to 3.5-5.

5.

5. The method for preventing aluminum nitride ceramic substrate from absorbing moisture and hydrolyzing in DCB and AMB according to claim 1, characterized in that: The standing time in the step 1 is 10 min to 20 min.

6. The method for preventing aluminum nitride ceramic substrate from absorbing moisture and hydrolyzing in DCB and AMB according to claim 1, characterized in that: In the step 2, the ratio of the pre-hydrolyzed n-dodecyltrimethoxysilane solution to pure water is 1-2:18-19.

7. The method for preventing aluminum nitride ceramic substrate from absorbing moisture and hydrolyzing in DCB and AMB according to claim 1, characterized in that: In the step 3, the soaking time is 15 min to 25 min.

8. The method for preventing aluminum nitride ceramic substrate from absorbing moisture and hydrolyzing in DCB and AMB according to claim 1, characterized in that: In the step 4, heating and drying are performed under nitrogen protection conditions.

9. The method for preventing aluminum nitride ceramic substrate from absorbing moisture and hydrolyzing in DCB and AMB according to claim 8, characterized in that: The drying temperature is 90℃~150℃.

10. The method for preventing aluminum nitride ceramic substrate from absorbing moisture and hydrolyzing in DCB and AMB according to claim 8, characterized in that: The drying time is 45min~60min.